Utilizing Information Technology in Knowledge Sharing to Enhance the Performance of Public Organizations - Umi Rusilowati; Rr Ayu Metarini; Denok Sunarsi (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to investigate the utilization of information technology in knowledge sharing as a means to improve the performance of public organizations. The background of the research emphasizes the growing importance of knowledge sharing in enhancing organizational performance in the public sector. With the rapid advancement of technology, leveraging information technology platforms has become crucial for effective knowledge management and sharing. The research employs a mixed-methods approach, combining qualitative and quantitative methods. The qualitative phase involves a comprehensive literature review to explore the theoretical foundations and best practices of knowledge sharing and the role of information technology in the public sector. Additionally, interviews and focus group discussions with key stakeholders from various public organizations will be conducted to gain insights into current knowledge sharing practices and the potential challenges faced. In the quantitative phase, a survey questionnaire will be administered to a sample of public organization employees to assess their perceptions of knowledge sharing practices and the impact of information technology on organizational performance. The collected data will be analyzed using appropriate statistical techniques to identify correlations and patterns between the variables. The anticipated findings of this research will contribute to a deeper understanding of the utilization of information technology in knowledge sharing and its impact on organizational performance in the public sector. The results will provide valuable insights for public organizations seeking to enhance their knowledge sharing practices and leverage technology effectively to achieve improved performance outcomes.